Development of Authentic Assessment instruments for Critical Thinking skills in Global Warming with a Scientific Approach - R. Surya Damayanti; Agus Suyatna; Warsono Warsono; Undang Rosidin (International Journal of Science and Applied Science: Conference Series, 2017)
This study aims to develop an authentic assessment instrument to measure critical thinking skills in global warming learning and to describe the suitability, easiness, and usefulness of the use instruments which are developed base on the teacher’s opinion.   The development design is carried out by Borg & Gall (2003) development model, which is conducted with seven stages: information gathering stage, planning stage, product development stage, product test stage, product revision stage, field trial stage, and final product. The test subjects are students and teachers in SMA Lampung Tengah by using purposive sampling technique.  Global warming learning using authentic assessment consists of a series of learning activities, including observing, discussing, exploring, associating and communicating.  The results show the authentic assessment techniques global warming to measure and cultivate critical thinking skills consisting of written tests, performance, portfolios, projects, and attitudes.  The developed assessment model meets content and constructs validity, and effectively improves students' critical thinking skills and has a high level of suitability, easiness, and usefulness well-being. The assessment techniques are used in global warming learning are performance assessment techniques, portfolios, projects, products, and attitude that together contribute to the improvement of critical thinking skills on 97,4% of global warming learning.